Persetujuan Majelis Kehormatan Notaris Wilayah Dalam Pengambilan Minuta Akta Dalam Proses Peradilan - Andi Nurfajriani Riandini Arief; Syukri Akub; Syamsuddin Muchtar (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2019)
This study aims to examine the importance of the approval of the Regional Notary Honorary Council in taking photocopies of the minuta notary deed for examination in criminal cases carried out by notaries and inspection mechanisms by the Regional Notary Honorary Council in approving alleged criminal acts committed by Notaries. This research is empirical juridical research. The results of the study show that the Honorary Board of Notaries in the South Sulawesi Province still get obstacles in carrying out their duties and functions, especially in giving decisions both in approval and rejection of requests from law enforcement officials. Based on the results of the study the authors inventory the obstacles that come from notaries and law enforcement officials as well as in terms of legal rules. The suggestion in the future is the need for continuous guidance to notaries and law enforcement officials so that both parties can understand their respective positions in carrying out the profession as well as understanding the duties and functions of the Regional Notary Honorary Council.